Algebra 1

Published by Prentice Hall
ISBN 10: 0133500403
ISBN 13: 978-0-13350-040-0

Chapter 5 - Linear Functions - 5-5 Standard Form - Mixed Review: 72

Answer

$y-2 = 4/3*(x-3)$ $y = 4/3*x -2$

Work Step by Step

given: (0, -2) and (3,2) $y-y_{1} = m*(x-x_{1})$ $m = (2--2)/(3-0)$ $m = 4/3$ $y-y_{1} = m*(x-x_{1})$ $y-2 = 4/3*(x-3)$ $y-2 = 4/3*(x-3)$ $y-2 = 4/3*x - 4$ $y-2 + 2 = 4/3*x - 4 + 2$ $y = 4/3*x -2$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.